Utilization Of Air Pollution As An Alternative For Growing Galah Shrimp (Macrobracium rosenbergii) In The Minapadi System Hydroganic - Mahendra, Mahendra; Dina Febrina, Citra (Publisher Cv. Inara, 2024)
This research aims to increase farmers' income with high rice productivity and increase shrimp production. The method used was a Completely Randomized Design (CRD) experiment with 3 treatments and 4 replications. The treatments are: P1 (air pollution made from jengkol), P2 (air pollution made from noni), and P3 (air pollution made from garlic). This research was carried out for 100 days in the Teuku Umar University campus area using budikdamber aquaponics. The parameters observed were shrimp growth and survival. The research results showed that the best treatment was P2 which produced an average growth value for giant prawns of 3.42 g/ fish. From the results of this research, the application of air pollution with giant prawns has a positive impact on the observed parameters (P <0.05) and provides benefits for farmers.